Forest owners and attitudes towards conservation policy in Sweden - Riviere, Miguel (2016)
In 1993, Sweden issued a new forestry act, which gives equal importance to timber production and nature protection, and uses a wide range of policy tools, known as the Swedish forestry model, to achieve its goals. However, there is evidence that the Swedish forestry model does not perform as well as expected, especially regarding the involvement of Non Industrial Private Forest owners (NIPFs) in conservation. To better understand this situation, this thesis project investigates NIPFs' values, backgrounds and attitudes towards conservation and the Swedish forestry model by realizing an owner typology. Using data from a national survey on NIPFs, Principal Component Analysis (PCA) and the K-means clustering method are used to identify groups of NIPFs based on their reasons for owning forests. Background information about the owners and their forests are compared among owner groups, as well as their attitudes towards conservation, towards the Swedish forestry model and their knowledge of environmental issues. Results reveal the existence of five owner groups with significantly different motivations and backgrounds. Environmental values constitute the main factor that differentiates NIPFs regarding their motivations, while economic and traditional values influence their attitudes and knowledge the most. Overall, the Swedish forestry model is well accepted by all owners, but differences appear regarding acceptance of state intervention, individual commitments to conservation and knowledge of environmental issues.